Effects of nanoplastics on antioxidant and immune enzyme activities and related gene expression in juvenile Macrobrachium nipponense - Li, Yiming; Liu, Zhiquan; Li, Maofeng; Jiang, Qichen; Wu, Donglei; Huang, Youhui; Jiao, Yang; Zhang, Meng; Zhao, Yunlong (Journal of hazardous materials, 2020)
[Display omitted] •The effects of polystyrene nanoplastics on juvenile M. nipponense were evaluated.•Nanoplastics reduced the survival rate of juvenile shrimp.•Nanoplastics induced oxidative stress and stimulated immune defense in shrimp.•High concentrations of nanoplastics had toxic effects on shrimp viability. Nanoplastics are widely distributed in aquatic environments, and nanoplastic pollution has become a global concern. However, few studies have evaluated the toxicity of nanoplastics to freshwater crustaceans. In this study, by adding different concentrations of nanoplastics to water, we explored the effects of nanoplastics on the survival, antioxidant activity, immune enzyme activity, and related gene expression levels in juvenile Macrobrachium nipponense. The results showed that the 96 -h half-lethal concentration of nanoplastics to juvenile shrimp was 396.391 mg/L. As the concentration of nanoplastics increased, the activities of antioxidant enzymes generally decreased, while the contents of hydrogen peroxide and lipid peroxidation products increased. The activities of non-specific immune enzymes first increased and then decreased with increasing nanoplastic concentration. The trends in the expressions of antioxidant-related genes were generally consistent with those in the activities of antioxidant enzymes. As the nanoplastic concentration increased, the expressions of immune-related genes generally increased at first and then decreased. These results indicate that low concentrations of nanoplastics (5 mg/L) may enhance the viability of juvenile shrimp, whereas high concentrations (10,20, 40 mg/L) have inhibitory and/or toxic effects. The findings provide basic information on the toxic effects of nanoplastics in juvenile shrimp.